2021
DOI: 10.7717/peerj.11854
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quantitative relationships between the impervious surface area and surface heat island effect during urban expansion

Abstract: As an important component of underlying urban surfaces, the distribution pattern and density of the impervious surface area (ISA) play an important role in the generation of surface urban heat island (SUHI) effects. However, the quantitative and localized exploration of the ISA’s influence on SUHIs in the process of urban expansion from the perspective of temporal and spatial changes is still not clear. Based on multisource remote sensing data, the SUHI effect of urban expansion is revealed by using geospatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…By comparing Tables 2 and 3, it could be seen that when considering the interactions between IFs in the summer model, the cooling impact of IPS on LST became insignificant. On the contrary, as shown in Figure 6e, IPS exhibited a significant warming effect on the land surface in the autumn model based on MGAMI, which was more consistent with the findings reported in the literature [12,63]. It was also found that the significant effect of WB disappeared in the spring model based on MGAM when considering the influence of interactions between IFs.…”
Section: Discussionsupporting
confidence: 90%
“…By comparing Tables 2 and 3, it could be seen that when considering the interactions between IFs in the summer model, the cooling impact of IPS on LST became insignificant. On the contrary, as shown in Figure 6e, IPS exhibited a significant warming effect on the land surface in the autumn model based on MGAMI, which was more consistent with the findings reported in the literature [12,63]. It was also found that the significant effect of WB disappeared in the spring model based on MGAM when considering the influence of interactions between IFs.…”
Section: Discussionsupporting
confidence: 90%
“…According to the characteristics of different thermal infrared remote sensing data, there are three main types of land surface temperature retrieval algorithms: atmospheric correction method, single-channel algorithm and split window algorithm [20,26,40]. In this paper, the atmospheric correction method suitable for Landsat satellite imagery is used to retrieve the surface temperature of the thermal infrared bands of TM and TIRS.…”
Section: Inversion Of Surface Temperaturementioning
confidence: 99%
“…Based on the existing remote sensing image data, we build a 100 × 100 fishing net in ArcMap software to generate sampling points. Then extract the LULC pixel value to the center of the grid and use this value as one of the input parameters of ANN [26]. Similarly, we extracted the LST, NDBI, NDBSI, longitude and latitude of the main urban area of Wuhan in 2000, 2011 and 2020 respectively.…”
Section: Ann Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the expected rising temperature, many researchers agree that the lack of green areas in favour of large impervious surfaces that absorb more energy and cool more slowly is one of the main reasons that heat stress is higher in cities [5,6], along with the fact that building elevations and density reduce wind speed (air flow) and prevent heat dispersion [7][8][9]. In addition, human activities such as heating/cooling buildings and driving cars warm the environment.…”
Section: Introductionmentioning
confidence: 99%